Netresearch : finding information online - Barrett, Daniel J. (Sebastopol, CA : Songline Studios : O'Reilly & Associates, 1997)
In NetResearch, you'll learn successful search techniques that work with any Internet search programs, present or future, by using your instincts to track down what you need. Intuition, unlike printed lists of sites and obscure search-engine commands, doesn't go out of date - it grows. NetResearch presents strategies of the Internet's expert searchers: how to choose effective starting points, follow hunches, narrow down possibilities, and even overcome failure by looking at search possibilities from different viewpoints. Whatever your profession or avocation, NetResearch teaches you how to locate the information you need in the constantly changing online world. It covers the Internet, America Online, CompuServe, Microsoft Network, and Prodigy, and includes quizzes for practicing your research skills or teaching others how to search effectively.
Ch. 1. Instant Gratification...and Beyond -- Ch. 2. Internet Basics -- Ch. 3. Views of the Internet -- Ch. 4. Choosing an Effective Starting Point -- Ch. 5. Web Searching Techniques -- Ch. 6. Finding Places -- Ch. 7. Finding People -- Ch. 8. Finding Kindred Spirits -- Ch. 9. Finding Freely Distributable Software -- Ch. 10. Finding Information Again -- Ch. 11. Putting Information Online.
Includes index.
Includes index.
Koleksi sumbangan Prof. Dr. Ding Choo Ming.
Keywords: Internet; Information retrieval; Database searching; World Wide Web; Computer networks